(untitled) (Faridpur Medical College Journal, 2018)
Acute liver failure (ALF) is a severe condition leading to fatal complications and death. Early detection and proper management can save life. The aim of the study was to analyze different biochemical values in acute liver failure and its relation with outcome. This study was conducted over 64 admitted patients in two medical college hospitals for duration of one and half year from December 2013 to May 2015. At presentation S. bilirubin level was in the range of 5-20 mg/dl in 46 (71.88%), S. ALT level in the range of 100 - 500 U/L in 46 (71.88%) and prothrombin time more than 22 seconds in 40 (62.50%) patients. Among other biochemical values S. creatinine was >1.5 mg/dl in 14 (21.88%), random blood glucose level < 2.5 mg/dl in 12 (18.75%) and hyponatremia in 20 (43.48%) patients. Majority (56.25%) of patients were HEV positive. Mortality was 100% in patients with S. bilirubin, S.ALT or prothrombin time level >10 mg/dl, >500 U/L and >21 seconds respectively at presentation. The higher the liver biochemical values the higher is the mortality rate. More multicentre study with large sample size is recommended to make a concrete comment. Faridpur Med. Coll. J. Jan 2018;13(1): 17-19